2013
DOI: 10.1016/j.redox.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Aging-dependent changes in rat heart mitochondrial glutaredoxins—Implications for redox regulation

Abstract: Clinical and animal studies have documented that hearts of the elderly are more susceptible to ischemia/reperfusion damage compared to young adults. Recently we found that aging-dependent increase in susceptibility of cardiomyocytes to apoptosis was attributable to decrease in cytosolic glutaredoxin 1 (Grx1) and concomitant decrease in NF-κB-mediated expression of anti-apoptotic proteins. Besides primary localization in the cytosol, Grx1 also exists in the mitochondrial intermembrane space (IMS). In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…Although this result is comparable with our previously data (Boengler et al . ), others have reported higher RCR ratios (Chen et al ., ; Asemu et al ., ; Gao et al ., ). This could be due to either measuring oxygen consumption at 30°C instead of 25°C, using trypsin instead of nargase to release the IFM or stimulating the mitochondria with higher concentration of ADP than what was used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Although this result is comparable with our previously data (Boengler et al . ), others have reported higher RCR ratios (Chen et al ., ; Asemu et al ., ; Gao et al ., ). This could be due to either measuring oxygen consumption at 30°C instead of 25°C, using trypsin instead of nargase to release the IFM or stimulating the mitochondria with higher concentration of ADP than what was used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…However, gene expression of the thioredoxin system was unaltered in Glrx -/-mice. Furthermore, the mitochondrial isoform glutaredoxin-2, which is exclusively mitochondrial matrix localized (54) and controls ironsulfur clusters (24) as well as mitochondrial protein GSH adducts (19), showed no changes in gene expression.…”
Section: Glrxmentioning
confidence: 96%
“…However, most of the Grx2 is prominently in the inactive dimer formation. Only by exogenous superoxide production by xanthine oxidase was the dimer able to cleave to monomeric form [43]. H 2 O 2 had no effect on Grx2 activation.…”
Section: Cardiovascular and Immune Systemsmentioning
confidence: 93%
“…Usually, with aging, there is a decline in antioxidant expression and activity. Interestingly, Gao et al first suggested that Grx2 is found to be increased nearly twofold in the mitochondrial matrix of cardiac muscle cells [43]. However, most of the Grx2 is prominently in the inactive dimer formation.…”
Section: Cardiovascular and Immune Systemsmentioning
confidence: 99%